Parents' pandemic stress, parental involvement, and family quality of life for children with autism - Cheng, Shengli; Cheng, Sanyin; Liu, Shushan; Li, Yun (Frontiers in Public Health, 2022)
Background Research has shown that parents of children with autism spectrum disorder (ASD) suffered high levels of stress during the COVID-19 pandemic and faced poor family quality of life (FQOL). However, little is known about the inherent dynamic interaction between pandemic stress and FQOL, especially in the Chinese cultural context. Aims This study provides preliminary evidence by examining the relationships among pandemic stress, parental involvement, and FQOL for children with autism in mainland China. Method A total of 709 parents of children with autism completed measures of FQOL, parental involvement, and pandemic stress. Structural equation modeling was employed to examine the interrelations among these variables. Results Pandemic stress has direct effect and indirect effect mediated by parental involvement on FQOL. Two dimensions of pandemic stress had a direct effect on FQOL (β1 = 0.11; β2 = −0.55) and three dimensions had an indirect effect on FQOL through parental involvement (β1 = −0.097; β2 = 0.257; β3 = 0.114). Conclusion Stress related to the COVID-19 pandemic affects family quality of life for children with autism in complex ways. Policies may be developed to enhance parental pragmatic hopefulness in the anti-epidemic victory and alleviate negative physical and mental reactions caused by the pandemic.